Problematic trading: a Systematic Review of theoretical considerations - Loscalzo, Yura; Rogier, Guyonne; Velotti, Patrizia (Frontiers in Psychiatry, 2025)
Background and aimsRecently, the psychological literature increased attention to problematic financial trading, usually adopting the behavioral addiction framework aprioristically. Therefore, we aim to systematize the theoretical literature across different scholarly areas to detect if there is an accurate theorization and operationalization of the construct that considers the features of problematic trading.MethodsWe used six scientific databases (MEDLINE, PsycARTICLES, PsycINFO, PubMed, Scopus, and Web of Science). We found that 23 papers met our eligibility criteria.ResultsOur systematic review showed that problematic trading received attention since the ‘90s in the economy/law area. However, none of the 11 non-psychological papers conceptualized problematic trading as a phenomenon on its own. Regarding instead the psychological literature, ten up to 12 papers used the behavioral addiction framework, usually assimilating problematic trading to gambling. Moreover, only four papers conceptualized it as a distinct diagnosis from gambling.Discussion and conclusionsEven if the psychological literature seems to begin supporting the conceptualization of problematic trading as a disorder on its own, there is a tendency to assimilate it into gambling. We recommend that future studies analyze problematic trading as a distinct phenomenon and avoid the aprioristic use of the gambling framework to unveil the features of this new potential clinical disorder. Thus, qualitative studies for in-depth knowledge of problematic trading would be critical before suggesting a specific operationalization of the construct and a scale of measure.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD4202455828, identifier CRD42024558280